1993
DOI: 10.1007/bf00318610
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and morphometry of testicular Leydig cells and the interstitial components correlated with testosterone in aging rats

Abstract: The ultrastructure of testicular interstitium in young and aged adult rats was analysed using morphometric methods, and the plasma testosterone concentration was measured. With increasing age there was an augmentation in the volume of collagen fibrils in the intercellular matrix and in blood vessels. During the aging process (approximately two years) the average volume of the Leydig cell decreased from 1364 microns 3 to 637 microns 3, but the number of Leydig cells in paired testes increased from 53 x 10(6) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 41 publications
7
31
0
1
Order By: Relevance
“…These changes are indicative for disturbed communication between seminiferous epithelium and interstitium and imply the altered testicular trophic during aging that might be responsible for dysfunction of blood-testis barrier and germ cell depletion [23]. Our findings are in concert with data for increased collagen deposition in testicular interstitium [24] and decreased tubular volume, diameter and length as well as luminal volume [25] of aged testis.…”
Section: Discussionsupporting
confidence: 78%
“…These changes are indicative for disturbed communication between seminiferous epithelium and interstitium and imply the altered testicular trophic during aging that might be responsible for dysfunction of blood-testis barrier and germ cell depletion [23]. Our findings are in concert with data for increased collagen deposition in testicular interstitium [24] and decreased tubular volume, diameter and length as well as luminal volume [25] of aged testis.…”
Section: Discussionsupporting
confidence: 78%
“…When specifically challenged in vitro, isolated Leydig cells of older rats of several different strains show significantly less steroidogenic response to tropic hormone stimulation than do cells from young animals [162,175,178,[181][182][183]. Only studies conducted by Kaler and Neaves [177] reported no significant differences in testosterone production by isolated Leydig cells from old rats as compared to similarly isolated cells from young controls [177].…”
Section: Experimental Animalsmentioning
confidence: 98%
“…In contrast, occurrence of Leydig cell hyperplasia as a consequence of aging has also been reported in stallions [179] and humans [141]. Other studies suggest that Leydig cells undergo atrophic changes in size [168,169,176,180] and organelle content [178] with aging. Bethea and Walker [181] provided evidence showing that aging leads to decreased Leydig cell mass, at least in testis of Fischer rats.…”
Section: Experimental Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Wang et al 18 demonstrated that the number of LCs in old rats (up to 21 months of age) is not lower than the number of LCs in young rats, and Chen et al 19 detected no difference in the number of LCs upon stereological analysis. Thus, the decline in TT levels with age cannot be explained by loss of LCs 17,21 ; this change is the result of LCs dysfunction rather than death 7 .…”
mentioning
confidence: 99%